A Green Approach to Odour Control: Development of a Natural-Ingredient Deodorant Formulation Enriched with Plant-Based Bioactives - Fatin Farisha Mohd Yusoff,; Angzzas Sari Mohd Kassim, (Progress in Engineering Application and Technology, 2026)
Conventional deodorant products commonly rely on synthetic antimicrobial agents and fragrance systems, raising concerns regarding skin compatibility, disruption of the axillary microbiome and environmental sustainability. This study aimed to develop and evaluate a natural-ingredient deodorant formulation enriched with plant-based bioactives as a green approach to underarm odour control. The scope of the research involved screening selected natural actives, namely magnesium hydroxide, zinc ricinoleate, kaffir lime essential oil, rose essential oil and tea tree essential oil, for their functional properties and incorporating the most effective bioactives into prototype deodorant formulations. Antimicrobial activity against Staphylococcus sp. was evaluated using agar diffusion assays, while antioxidant capacity was assessed using DPPH and FRAP methods. The formulated deodorants were further characterized in terms of pH, texture, spreadability and stability under selected storage conditions. The results demonstrated that the plant-based bioactives exhibited measurable antimicrobial activity with inhibition zones ranging 14.5 ± 0.29 to 28.3 ± 0.33 mm and antioxidant activity between 0.235 ± 0.001 and 0.269 ± 0.001 AU at 517 nm. The selected deodorant formulations showed skin-compatible pH values (7.5-9.4), acceptable physical stability and retention of functional properties. In conclusion, the findings support the feasibility of incorporating plant-based bioactives into natural deodorant formulations as a skin-friendly and sustainable odour control alternative.